Patient Preferences for Code Status Discussions: A Randomized Trial of Information- vs. Patient Values-Centered Frameworks - Joshi, Christopher; Malik, Sehrish; Wang, Wei; Ouchi, Kei (Journal of general internal medicine : JGIM, 2025)
Helping patients make decisions about their preferences for cardiopulmonary resuscitation (i.e., code status) is an important way to respect patient autonomy in the hospital. There is a gap in understanding which framework of discussion patients prefer for this decision-making. To determine which of two frameworks to code status discussions-information-centered or patient values-centered-make patients feel more heard and understood about their preferences regarding cardiopulmonary resuscitation (CPR). Prospective, randomized study comparing two different frameworks to CPR discussion. We enrolled adult patients with one or more serious illnesses who were recently discharged from an urban, tertiary care, academic medical center in Boston, MA. Subjects were randomized to receive either the information-centered framework, in which their likelihood of recovery following CPR was shared, or the patient values-centered framework, in which their personal values were elicited and used to make a recommendation. Subject-reported heard and understood rating with regard to their preferences for CPR. Of the 46 subjects enrolled, 25 (54.3%) were male, 42 (91.3%) were White, and 3 (6.5%) were Black. Mean age was 66.4 ± 11.8 years. Subjects reported feeling more "heard and understood" about their preferences for CPR with the patient values-centered framework compared with after the information-centered framework (p = 0.033). When asked, 89% of subjects "definitely" or "probably" wanted to hear their doctor's personalized recommendation about CPR (p < 0.001). Patients, in line with palliative care experts, largely support a patient values-centered framework to CPR, including a recommendation made by the clinician based on the patient's expressed values.